Réponses

2014-01-24T18:04:55+01:00
Bonsoir

a) 4x² - 16x = 0
4x(x - 4) = 0
4x = 0   ou   x - 4 = 0
x = 0   ou  x = 4

S={0 ; 4}


b) 9x² - 36 = 0 
(3x + 6)(3x - 6) = 0  en appliquant la formule : a² - b² = (a + b)(a - b)
3x + 6 = 0   ou   3x - 6 = 0
3x = -6   ou  3x = 6
x = -6/3   ou   x = 6/3
x = -2   ou   x = 2

S = {-2 ; 2}
 
c) 25x² = 4
25x² - 4 = 0
(5x + 4)(5x - 4) = 0  en appliquant la formule : a² - b² = (a + b)(a - b)
5x + 4 = 0   ou   5x - 4 = 0
5x = -4   ou   5x = 4
x = -4/5   ou   x = 4/5

S = {-4/5 ; 4/5}